2008
DOI: 10.1002/crq.210
|View full text |Cite
|
Sign up to set email alerts
|

Skills needed to help communities manage natural resource conflicts

Abstract: Competition for natural resources has spawned unprecedented conflict between users, resulting in litigious and legislative actions. Citizens often expect Cooperative Extension professionals to engage communities in collaborative processes to manage these conflicts. This paper examines thirty‐five skills Cooperative Extension professionals need if they are to engage communities in collaborative processes. Survey methodology is used to assess the skills extension professionals perceive as most needed, and the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The training focused on three central skills, previously identified in an empirical study for this specific context (i.e. collaborative process skills, science and conflict skills and monitoring and evaluation skills; Singletary et al , 2008). The curriculum included lectures, case studies and a simulation.…”
Section: Theorymentioning
confidence: 99%
“…The training focused on three central skills, previously identified in an empirical study for this specific context (i.e. collaborative process skills, science and conflict skills and monitoring and evaluation skills; Singletary et al , 2008). The curriculum included lectures, case studies and a simulation.…”
Section: Theorymentioning
confidence: 99%
“…For instance, Mbiba and Huchzermeyer [62] noted that peri-urban areas in Africa are dominated by land-related disputes. Though there are locational variations, land can be seen as the direct or indirect source of most disputes in agrarian societies [52,63,64]. In most developing countries, even if horizontal urban expansion is the major cause of peri-urban land disputes [38], the problem is exacerbated in situations where there is a lack of sound spatial planning and where there are institutional problems, inadequate compensation payments, and the absence of effective land tenure security for all landholders [6,49,65].…”
Section: Land Tenure Disputesmentioning
confidence: 99%
“…A factor analysis of critical skills needed to assist communities manage natural resource conflicts conducted by Singletary et al. () assisted us in bringing coherence to these challenges and organizing around three broad sets of skills that are important for professionals to master. These are (a) collaborative process skills—enabling parties to understand themselves and the other to collaboratively problem solve—as well as solid facilitation and active listening skills, (b) science and conflict skills—including being able to manage complicated data in a negotiation as well as enabling parties to grapple with scientific uncertainty, and (c) monitoring and evaluation skills—including being able to adaptively manage a negotiation and likewise understanding how to assist parties through the implementation phase.…”
Section: Model Designmentioning
confidence: 99%
“…However, the development of new pedagogical approaches remains an important area for development. Other research has demonstrated that there is a profound need to develop curricula and pedagogies that enable professionals to engage parties in dynamic and collaborative processes for managing environmental and public policy conflicts (Patton & Blaine, ; Singletary et al., ) that rely on synthesized skills and knowledge from multiple practice and theoretical approaches (Daniels & Walker, ). We have explored the changing nature of increasingly complex real‐world situations calling for new and innovative ways to address these multi‐issue, multiparty negotiations.…”
Section: Future Directions and Opportunities To Adapt The Teaching Fomentioning
confidence: 99%